The Legal Theory of Investment Regimes - A. M. Lapteva (Теоретическая и прикладная юриспруденция)
This article is devoted to identify the features of the legal regulation of investment activity from the point of view of the concept legal regime. It should be stressed that such type the investment research is shown us the specific it’s regulation, the ratio of imperativeness and dispositivity and also the subjects activity level of the investment.The article analyzes and systematizes the doctrinal point of view on the concept of “legal regime”, it’s features and structure. The author’s definition of the investment regime is formulated, by which it is proposed to understand the procedure for regulating investment activity, expressed in a set of legal means characterizing a combination of interacting permits, prohibitions, as well as positive obligations and creating a special focus on regulating investment activity. The investment regime, according to the author, is a kind of legal regime.